PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KINERJA KARYAWAN PADA SUPERMARKET LIGO MITRA PONTIANAK - Salsa Bela Mailani; Achmadi Achmadi; Husni Syahrudin (Universitas Tanjungpura, 2022)
The purpose of this study is to investigate and evaluate how both the physical and non-physical work environment affect employee performance. A correlation research method is the type ofquantitative study that was used. 62 employees made up the study's sample. Multiple linear regression analysis, simple random sampling,and a questionnaire were all used in this study's data analysis and data gathering (questionnaire). According to the findings of multiple linear regression analysis, both the physical and non-physical work environments have a discernible impact on employee performance.The results of parallel tests indicate that both the physical and non-physical work environments have an impact on employeenperformance. According to the results of the analysis of the physicalbwork environment variable, which were obtained at count of 5.995 and Table of 2.001, there is a positive and substantial influence. Thestudy of multiple linear requirements, where the findings obtained in count are 2.187 and Table are 2.001 from non-physical worknenvironments on employee performance, shows that the results of the analysis of non-physical work environment variables have a positive and significant influence.